Analysis of laminated adaptive plate structures using layerwise finite element models - Garção, José (2010)
A general finite element formulation using the layerwise theory is developed for the analysis of laminated plate structures with piezoelectric layers or patches. The formulation considers small deformations and linear elastic material behaviour, and includes full electromechanical coupling. Several approximations of the primary variables in the thickness direction and different interpolation schemes in the surface directions are considered. This study illustrates the importance of the thickness approximation and provides a comparison between layerwise theories with different along the thickness direction approximations for the problem variables. The predictions of the displacement components, electrical potential, stress components and electrical displacement components are compared with three-dimensional, closed-form solutions for two benchmark problems. A very good agreement is obtained for the models using cubic approximation in the thickness direction. The accuracy of these models in the prediction of layer stresses is fully illustrated.